Resilient Institutions: The Impact of Rule Change on Policy Outputs in European Union Decision-Making Processes - Ripoll Servent, Ariadna (2021)
The evolution of the inter-institutional balance of powers has been a constant feature of the European integration process. Therefore, this thematic issue reopens these theoretical and empirical discussions by looking at an underexploited angle of research, namely the impact of rule change on policy outputs. We offer a discussion on how to theorise rule change, actors’ behaviour, and their impact on policy outputs. We also examine the links between theory and methods, noting the strengths and weaknesses of different methods for the study of institutional and policy change. We draw on the contributions of this thematic issue to delineate further paths to push forward the current frontiers in EU decision-making research.